Performance of Mixed Matrix Membrane Adsorbers for Lysozyme Separation - Saiful, Saiful (Jurnal Rekayasa Kimia & Lingkungan, 2011)
An application of EVAL based mixed matrix membrane adsorbers containing a strongcation exchange resins (Lewatit SP 112 WS) for capturing of Lysozyme (LZ) has been investigated.The preparation and performance of the mixed matrix membrane adsorbers is studied with 1-octanol as additive. The membranes in this study are prepared by immersion precipitation out of a DMSO solution containing 14% EVAL and with or without 14% 1-octanol. All membranes contain 65% resin based on dry solids. The morphology of the membranes are characterized using scanning electron microscopy.The membrane structure demonstrated open and interconnected porous structure with large resin particles are distributed in membrane structure. The MMM adsorber proved high adsorption capacity for capturing and concentrating LZ in feed solution. The Mixed matrix membranes (MMM) concept was anticipated as a moderate process with an increasedcapacity and a maximum adsorption capacity of 166 mg LZ/g membrane. The MMM act in protein separations both as protein purifier and concentrator and is an attractive alternative for packed bed systems because of its high capacity, high throughput, robustness, and ease of scaling up.Keywords: Mixed Matrix Membrane (MMM), Lysozyme (LZ), Adsorption, Membrane adsorber